Musclelike joint mechanism driven by dielectric elastomer actuator for robotic applications. (31st May 2018) - Jung, Ho Sang; Cho, Kyeong Ho; Park, Jae Hyeong; Yang, Sang Yul; Kim, Youngeun; Kim, Kihyeon; Nguyen, Canh Toan; Phung, Hoa; Hoang, Phi Tien; Moon, Hyungpil; Koo, Ja Choon; Choi, Hyouk Ryeol
Abstract: The purpose of this study is to develop an artificial muscle actuator suitable for robotic applications, and to demonstrate the feasibility of applying this actuator to an arm mechanism, and controlling it delicately and smoothly like a human being. To accomplish this, we perform the procedures that integrate the soft actuator, called the single body dielectric elastomer actuator, which is very flexible and capable of high speed operation, and the displacement amplification mechanism called the sliding filament joint mechanism, which mimics the sliding filament model of human muscles. In this paper, we describe the characteristics and control method of the actuation system that consists of actuator, mechanism, and embedded controller, and show the experimental results of the closed-loop position and static stiffness control of the robotic arm application. Finally, based on the results, we evaluate the performance of this application.